The High-Resolution Infrared Spectrum of the set of weak bands of trans-d2-Ethylene in the region 1450-1750 cm-1; Optoelectronics, Photonics, Engineering and Nanostructures (Saint Petersburg OPEN 2016) - Zyatkova (Ziatkova) A. G. Anastasiya Georgievna (2016, 2016)
Title screen